The Politics and Contestations of Argentina’s Tenant Organisations: Legislative Activism in a Homeownership Society - Joseph Palumbo (Critical Housing Analysis)
In recent years, the situation of renter households has emerged as a pressing social issue in Argentina, leading to the growth of tenant organisations around the country. This article examines the experience of grassroots tenant organisations in their attempts to influence local and national legislative agendas related to rental housing. It critically analyses these organisations’ concrete aims and achievements, as well as the other effects of this social movement. These include the emergence of novel forms of political mobilisation centred around the identity of ‘tenant’ in a country that still imagines itself as a homeownership society despite shifts in patterns of housing tenure and a budding ‘generation rent’.